Perioperative Care of Patients Undergoing Surgery During Coronavirus Pandemic - Hatanaka, Diná Mie; Valim, Livia Maria; Ferreira, Carolina Baeta Neves Duarte Ferreira; Echenique, Leandro; Leão, Fabiola Alves de Souza; Teruya, Alexandre (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
While the coronavirus-19 has already infected over 2.2 million patients and killed over 150 thousand people worldwide, in Brazil, there are now 374 thousand confirmed cases and 23 thousand casualties. Apparently, the country has not yet reached the expected peak of infections, based on the experience of previously affected countries. Many considerations have been made concerning surgical cases during the COVID pandemic. Some recommendations include delaying all electives cases to save beds, equipment, and medical staff for COVID-19 infected patients. At the same time, it is known that not all elective cases are optional. Surgery cancellation may, eventually, be deleterious to the patient. Urgent and emergency procedures will still have to be undertaken and are of great concern since noninfected subjects can be infected by the coronavirus-19 during hospitalization and, likewise, asymptomatic COVID-19 infected patients may be operated and spread the virus to the environment, contaminating the medical team and other patients. The purpose of this article was to discuss whether elective surgeries should be performed and, if performed, what precautions should be taken in order to protect both the patients and the hospital staff. Also, the conduction of urgent cases will be addressed.